Multilingual Practices in Academic Communities: Exploring Code-Switching as Social Action - Dewi Yanti (EXPOSE (Journal of English Education and for Specific Purpose), 2025)
This study aims to investigate multilingual language practices in an academic environment from a sociolinguistic perspective, with particular attention to language choice, code-switching, and code-mixing in both academic and social interactions. The research seeks to understand how multilingual speakers employ linguistic resources strategically to negotiate meaning, express identity, and achieve communicative goals. A qualitative descriptive research design was adopted to capture naturally occurring language use and its social functions. Data were collected through non-participant observations, semi-structured interviews, and documentation of spoken interactions among undergraduate students. The collected data were analyzed using an interactive qualitative analysis model involving data reduction, data display, and conclusion drawing. The findings indicate that language choice is highly context-dependent and influenced by factors such as interactional setting, topic, and participant roles. Indonesian functioned as the primary language of interaction, while English and Arabic were frequently used in academic discussions, particularly for technical terms and conceptual explanations. Code-switching and code-mixing were found to occur systematically and served important communicative functions, including academic clarification, identity construction, and the expression of social solidarity. These multilingual practices reflected speakers linguistic competence rather than language deficiency. The study concludes that multilingual language use in academic settings constitutes a form of social action embedded in everyday interaction. Code-switching and code-mixing should therefore be understood as legitimate and meaningful communicative strategies. By adopting a sociolinguistic lens, this research contributes to a more inclusive understanding of multilingualism and highlights the need to reconsider normative attitudes toward language use in higher education contexts.